The Impact of Luxury Functional Value on Purchase Intention: Determinant of Consumers´ Luxury Value Perceptions - Brito, Catarina Filipa Gomes de (2024)
Dissertation presented as the partial requirement for obtaining a Master's degree in Data Driven Marketing, specialization in Digital Marketing and Analytics